Contemporary Capitalism and its Crises : Social Structure of Accumulation Theory for the 21st Century / [electronic resource] - McDonough, Terrence; Reich, Michael; Kotz, David M. (Cambridge : Cambridge University Press, 2010)
This volume analyses contemporary capitalism and its crises based on a theory of capitalist evolution known as the social structure of accumulation (SSA) theory. It applies this theory to explain the severe financial and economic crisis that broke out in 2008 and the kind of changes required to resolve it. The editors and contributors make available new work within this school of thought on such issues as the rise and persistence of the 'neoliberal' or 'free-market' form of capitalism since 1980 and the growing globalization and financialization of the world economy. The collection includes analyses of the US economy as well as that of several parts of the developing world.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Capitalism; Saving and investment; Global Financial Crisis, 2008-2009